Human and rodent type 1 11beta-hydroxysteroid dehydrogenases are 7beta-hydroxycholesterol dehydrogenases involved in oxysterol metabolism. - Hult, M; Elleby, B; Shafqat, N; Svensson, S; Rane, A; Jörnvall, H; Abrahmsen, L; Oppermann, U (2004)
Interconversion between cortisone and the glucocorticoid receptor ligand cortisol is carried out by 11beta-hydroxysteroid dehydrogenase (11beta-HSD)isozymes and constitutes a medically important example of pre-receptor control of steroid hormones. The enzyme 11beta-HSD type 1 (11beta-HSD1) catalyzes the conversion of cortisone to its active receptor-binding derivative cortisol, whereas 11beta-HSD type 2 performs the reverse reaction. Specific inhibitors against the type 1 enzyme lower intracellular levels of glucocorticoid hormone, with an important clinical application in insulin resistance and other metabolic disorders. We report here on the in vitro oxysterol-metabolizing properties of human and rodent 11beta-HSD1. The enzyme, either as full-length, membrane-attached, or as a transmembrane domain-deleted, soluble form, mediates exclusively conversion between 7-ketocholesterol and 7beta-hydroxycholesterol with similar k(cat) values as observed with glucocorticoid hormones. Thus, human, rat, and mouse 11beta-HSD1 have dual enzyme activities like the recently described 7alpha-hydroxysteroid dehydrogenase/11beta-hydroxysteroid dehydrogenase from hamster liver, but differ fundamentally from the latter in that 7beta-OH rather than 7alpha-OH dehydrogenase constitutes the second activity. These results demonstrate an enzymatic origin of species differences in 7-oxysterol metabolism, establish the origin of endogenous 7beta-OH cholesterol in humans, and point to a possible involvement of 11beta-HSD1 in atherosclerosis.